Increased ICU mortality in septic shock patients with hypo- or hyper- serum osmolarity: A retrospective study - Gang Heng; Jiasi Zhang; Yi Dong; Yi Dong; Jiankun Jia; Benqi Huang; Yanbing Shen; Dan Wang; Zhen Lan; Jianxin Zhang; Tao Fu; Weidong Jin; et al. (Frontiers in Medicine, 2023)
BackgroundWhile many factors that are associated with increased mortality in septic shock patients have been identified, the effects of serum osmolarity on the outcomes of ICU patients with septic shock have not yet been studied.MethodsThe present study was designed to examine the association of serum osmolarity with ICU 28-day mortality in ICU patients with septic shock. Adult patients diagnosed with septic shock from the MIMIC-IV database were selected in this study. The serum osmolarity was calculated synchronously according to the serum concentrations of Na+, K+, glucose, and urea nitrogen.ResultsIn the present study, a significant difference was observed between the 28-day mortality of septic shock patients with hypo-osmolarity, hyper-osmolarity, and normal osmolarity (30.8%, 34.9%, and 23.0%, respectively, p < 0.001), which were detected at ICU admission. After propensity score matching (PSM) for basic characteristics, the relatively higher mortality was still observed in the hypo-osmolarity and hyper-osmolarity groups, compared to normal osmolarity group (30.6%, 30.0% vs. 21.7%, p = 0.009). Furthermore, we found that transforming the hyper-osmolarity into normal osmolarity by fluid therapy on day 2 and 3 decreased this mortality.ConclusionThe serum osmolarity disorder is markedly associated with increased 28-day mortality in septic shock patients.